Fibropreventive and Antifibrotic Effects of Uncaria gambir on Rats with Pulmonary Fibrosis. (26th June 2022) - Desdiani, Desdiani; Rengganis, Iris; Djauzi, Samsuridjal; Setiyono, Agus; Sadikin, Mohamad; Jusman, Sri Widia A.; Siregar, Nuryati Chairani; Suradi, Suradi; Eyanoer, Putri C.
Abstract : Pulmonary fibrosis causes scar tissue formation that disrupts the functioning of the lungs. Uncaria gambir (Hunter) Roxb (hereafter gambir)—a plant native to West Sumatra in Indonesia—contains flavonoid (+)-catechin, which has strong antioxidant activity and can be used to combat pulmonary fibrosis. This random in vivo experimental study analyzed the antifibrotic effect of gambir on the lungs of rats with bleomycin-induced fibrosis. The subjects were 10 groups of 10-week-old male rats weighing around 200–250 g. All groups were terminated at the end of the seventh week or on day 50. The lungs were cleaned, and tissues were taken to analyze inflammatory cell counts and TGF- β 1 levels using bronchoalveolar lavage (BAL) with ELISA; type I collagen and tissue inhibitor of metalloproteinase 1 (TIMP-1) levels using immunohistochemistry (IHC); and activation of NF- κ B using ELISA and Western blot assays. The most severe histopathological characteristic based on the modified Ashcroft score was in the bleomycin group (BG), whereas the mildest was in the 262 mg/kg of the bodyweight antifibrotic gambir-dosed group (AF G262). The results showed a significant difference in the BAL inflammatory cell count (p = 0.017 ; p < 0.05 ). AF G262 differed most from the other antifibrotic groups in terms of the number of inflammatory cells (0.63), TGF- β 1 levels (3.80), and NF- κ B levels (0.48), followed by the 131 mg/kg of the bodyweight antifibrotic gambir-dosed group (AF G131), which also differed most from other antifibrotic groups in terms of NF- κ B (0.48), TIMP-1 (11.74), and collagen I (14.50) levels. Western blot analysis showed that the fibropreventive and antifibrotic groups had a specific band size of p65, whereas no specific band binding existed in the control group. This study concluded that the administration of AF G262 could improve fibrosis by lysing the extracellular matrix (ECM) in rat lungs.